Eriodictyol as a Potential Candidate Inhibitor of Sortase A Protects Mice From Methicillin-Resistant Staphylococcus aureus-Induced Pneumonia - Wang, Li; Li, Qianxue; Li, Jiaxin; Jing, Shisong; Jin, Yajing; Yang, Lin; Yu, Hangqian; Wang, Dacheng; Wang, Tiedong; Wang, Lin (Frontiers in Microbiology, 2021)
New anti-infective approaches are urgently needed to control multidrug-resistant (MDR) pathogens, such as methicillin-resistant Staphylococcus aureus (MRSA). Sortase A (SrtA) is a membrane-bound cysteine transpeptidase that plays an essential role in the catalysis of covalent anchoring of surface proteins to the cell wall of Staphylococcus aureus (S. aureus). The present study reports identification of a flavonoid, eriodictyol, as a reversible inhibitor of SrtA with an IC50 of 2.229 ± 0.014 μg/mL that can be used as an innovative means to counter both resistance and virulence. The data indicated that eriodictyol inhibited the adhesion of the bacteria to fibrinogen and reduced the formation of biofilms and anchoring of staphylococcal protein A on the cell wall. The results of fluorescence quenching experiments demonstrated a strong interaction between eriodictyol and SrtA. Subsequent mechanistic studies revealed that eriodictyol binds to SrtA by interacting with R197 amino acid residue. Importantly, eriodictyol reduced the adhesion-dependent invasion of A549 cells by S. aureus and showed a good therapeutic effect in a model of mouse pneumonia induced by S. aureus. Overall, the results indicated that eriodictyol can attenuate MRSA virulence and prevent the development of resistance by inhibiting SrtA, suggesting that eriodictyol may be a promising lead compound for the control of MRSA infections.